Optical and transport properties of rare-earth trivalent ions located at different sites in sol-gel SnO2 - Morais, E. A. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Ravaro, L. P. [UNESP]; Li, Siu M.; Floriano, E. A. [UNESP] (IOP Publishing, 2010)
Photoluminescence and photo-excited conductivity data as well as structural analysis are presented for sol-gel SnO2 thin films doped with rare earth ions Eu3+ and Er3+, deposited by sol-gel-dip-coating technique. Photoluminescence spectra are obtained under excitation with various types of monochromatic light sources, such as Kr+, Ar+ and Nd:YAG lasers, besides a Xe lamp plus a selective monochromator with UV grating. The luminescence fine structure is rather different depending on the location of the rare-earth doping, at lattice symmetric sites or segregated at the asymmetric grain boundary layer sites. The decay of photo-excited conductivity also shows different trapping rate depending on the rare-earth concentration. For Er-doped films, above the saturation limit, the evaluated capture energy is higher than for films with concentration below the limit, in good agreement with the different behaviour obtained from luminescence data. For Eu-doped films, the difference in the capture energy is not so evident in these materials with nanoscocopic crystallites, even though the luminescence spectra are rather distinct. It seems that grain boundary scattering plays a major role in Eu-doped SnO2 films. Structural evaluation helps to interpret the electro-optical data. © 2010 IOP Publishing Ltd.
Keywords: Conductivity data; Dip coating techniques; Doped films; Electro-optical; Er-doped; Fine structures; Grain boundary scattering; Luminescence spectrum; Monochromatic light; ND : YAG lasers; Photoluminescence spectrum; Rare earth ions; Rare-earth doping; Structural evaluation; Trapping rate; Trivalent ion; Xe lamp; Building materials; Defects; Doping (additives); Erbium; Europium; Gels; Grain boundaries; Grain size and shape; Insulating materials; Krypton; Light sources; Metal ions; Monochromators; Neodymium lasers; Photoluminescence; Sol-gel process; Sol-gels; Sols; Structural analysis; Transport properties; Xenon; Films